2019
DOI: 10.3390/s19153256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Imperfections Due to Material Heterogeneity on the Offset of Polysilicon MEMS Structures

Abstract: Monte Carlo analyses on statistical volume elements allow quantifying the effect of polycrystalline morphology, in terms of grain topology and orientation, on the scattering of the elastic properties of polysilicon springs. The results are synthesized through statistical (lognormal) distributions depending on grain size and morphology: such statistical distributions are an accurate and manageable alternative to numerically-burdensome analyses. Together with this quantification of material property uncertaintie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The mean value and standard deviation for the obtained effective Young's modulus are: Under the Voigt assumption, = 150.0 GPa, = 5.5 GPa; under the Reuss assumption, = 148.1 GPa, = 5.4 GPa. An interesting feature of these results is that the mean values are very close to the average between the asymptotic Reuss and Voigt bounds; in [27], it was shown that the scattering in the solution around the mean is instead greatly affected by ℎ ⁄ . Similar results can also be attained for the other elastic moduli of the film, assumed to be in-plane isotropic (namely, transversely isotropic with the mentioned texture aligned with the out-of-plane direction) at varying ℎ ⁄ ratios.…”
Section: Resultsmentioning
confidence: 67%
“…The mean value and standard deviation for the obtained effective Young's modulus are: Under the Voigt assumption, = 150.0 GPa, = 5.5 GPa; under the Reuss assumption, = 148.1 GPa, = 5.4 GPa. An interesting feature of these results is that the mean values are very close to the average between the asymptotic Reuss and Voigt bounds; in [27], it was shown that the scattering in the solution around the mean is instead greatly affected by ℎ ⁄ . Similar results can also be attained for the other elastic moduli of the film, assumed to be in-plane isotropic (namely, transversely isotropic with the mentioned texture aligned with the out-of-plane direction) at varying ℎ ⁄ ratios.…”
Section: Resultsmentioning
confidence: 67%
“…As far as the elasticity of the polysilicon film is concerned, a model was proposed in [18]. Since the morphology varies along the beam axis in an unpredictable way, a Monte Carlo analysis was resorted to define the effective value of 𝐸 to be adopted in Equation (1).…”
Section: Stochastic Effects and Scattered Device Responsementioning
confidence: 99%
“…To speed-up the computation of the pdf of 𝐸, in [18] the pdfs for the elastic moduli given by the computational homogenization on the SVEs were fitted with lognormal distributions. In our analysis, we still allow for such pdfs even if they can introduce an approximation in the model.…”
Section: Stochastic Effects and Scattered Device Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Polysilicon, including both undoped and heavily doped polysilicon, has many important applications in complementary metal oxide semiconductor (CMOS) and micro electro mechanical systems (MEMS) technologies [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Compared to undoped polysilicon, heavily doped polysilicon has higher Seebeck coefficient, lower electrical resistivity and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%